Subtotal resection of the scapula due to a chondrosarcoma. - Estapé, Gonzalo; Cresseri, Aída; Sigliano, Héctor; Iraola, María L; Delgado, Bolívar (Cirugía del Uruguay, 1988)
An osteochondroma of the right scapula with sarcomatous transformation, disease with a very low frequency in foreign series, and exceptional in national ones, is presented.